A Novel Estimation Method in FDA-MIMO Radar Using Matrix Pencil Method - Liu, Feilong; Zhu, Shengqi; Xu, Jingwei; Li, Ximin; Wang, Yanxing; Chen, Zhuochen (2023 3rd International Conference on Frontiers of Electronics, Information and Computation Technologies (ICFEICT), 2023)
There has been a surge of interest in the research of frequency diverse array (FDA) radar across various radar-related fields. However, the current parameter estimation algorithms for FDA-MIMO radar demand a significant number of samples to estimate the covariance matrix. In this paper, a novel range and angle estimation with FDA-MIMO radar via matrix pencil method is proposed. Firstly, an augmented matrix is constructed by using the covariance matrix of received data obtained from a small sample. Secondly, the angle and range estimation for subject of interest through singular value decomposition and subspace theory. Finally, the simulation results indicate that the proposed algorithm presented in this paper exhibits superior performance in terms of estimation accuracy compared to the existing methods, especially when the signal-to-noise ratio is low and the number of snapshots is limited.